Penerapan Media Game untuk Meningkatkan Hasil Belajar Pemangkasan Rambut Siswa Kelas XI TTKR SMKN 1 Pogalan Trenggalek - Adelia Septina Ika Anggraini; Dewi Lutfiati; Octaverina Kecvara Pritasari; Nia Kusstianti (Program Studi Pendidikan Tata Rias, 2026)
The effectiveness, efficiency, and appeal of learning are utilized as benchmarks in determining digital game-based learning media to achieve optimal improvement in learning outcomes. The effectiveness of using game media assisted by QuizWhizzer was evaluated as an effort to strengthen students' understanding of uniform layer hair cutting material, which is the primary focus of this study. The Research and Development (R&D) cyclical model of Analysis, Design, Development, Implementation, and Evaluation (ADDIE) was applied in this research, followed by a true experimental method with a pretest-posttest control group design. Data were collected through observations of the feasibility of the learning media, assessments (cognitive, psychomotor, and affective tests), and student response questionnaires. A sample of 71 students was randomly selected from two classes and divided into the experimental group (XI TKKR 2) and the control group (XI TKKR 1). The feasibility and effectiveness of the QuizWhizzer game media proved capable of improving students' learning outcomes across all domains related to the uniform layer material. The experimental class using the game media demonstrated higher posttest scores compared to the control class. The positive responses received indicated that the game media could create a more engaging and interactive learning environment. Based on these findings, QuizWhizzer game media is proposed as an effective innovative alternative learning medium to support vocational education.